Effect of pH on Swelling Profile of Glutaraldehyde Crosslinked Adenanthera pavonina L. Galactomannan. Issue 1 (April 2020) - Cavalcante, L A; Batista, B S; Fonseca, A P G; Balteiro, A J D; Amaral, F M B; Mendes, F; Macêdo, A A M
Abstract: Galactomannans are neutral natural polymers isolated from legume endosperm and with wide use in the biomedical field. As a consequence, there is a need to investigate materials for their properties in order to better understand and apply them. In this study, we analyzed the influence of pH medium on the crosslinking process of galactomannan and glutaraldehyde, changing the pH medium from 3 to 7, using a strong base. The Fourier Transform Infrared Spectrum (FTIR) and the swelling profiles of the glutaraldehyde crosslinked galactomannan were evaluated. We have found that the glutaraldehyde-galactomannan crosslinking process is highly sensitive to the variation of pH medium. According to our results, best swelling capacity was achieved for samples prepared at pH=5, suggesting that this pH medium conditions is suitable for possible production of hydrogels prepared from glutaraldehyde-galactomannan.